Learning by Using Concept Maps in Classroom - Sarker, Prabir (Institute of Electrical and Electronics Engieers Inc, 2011)
A concept map is a graphical presentation of the network of concepts showing the relationships among them. This paper presents a case study where concept map was used in lectures of an engineering unit as a learning tool. Contents of the unit are analyses of civil engineering structures by using different methods. Solutions of structural analysis problems by different methods are based on certain key concepts and their applications following the right procedure. Concept maps were used in lectures to show the concepts and their associations involved in each method of solution. The maps were also used to show the differences and similarities among different methods of solutions. Students were engaged in classroom to construct concept maps to help solving problems. At the end of the semester, students were given questionnaires to give anonymous feedback on the usefulness of the concept maps to help their learning in the unit. Sixty six students provided feedback on the use of concept maps. It is shown by the students' responses that majority of the students found concept maps helpful in understanding the key concepts and their associations in each method of structural analysis. It also helped students to compare the different methods, to choose the right method and follow the right steps to solve a particular problem. Students wanted to see continued use of the concept maps in future since it introduced the key concepts and helped retain the knowledge. Therefore, the use of the concept maps in the lecture helped improve student learning.